Excess free histone H3 localizes to centrosomes for proteasome-mediated degradation during mitosis in metazoans. Issue 16 (17th August 2016) - Wike, Candice L.; Graves, Hillary K.; Wason, Arpit; Hawkins, Reva; Gopalakrishnan, Jay; Schumacher, Jill; Tyler, Jessica K.
ABSTRACT: The cell tightly controls histone protein levels in order to achieve proper packaging of the genome into chromatin, while avoiding the deleterious consequences of excess free histones. Our accompanying study has shown that a histone modification that loosens the intrinsic structure of the nucleosome, phosphorylation of histone H3 on threonine 118 (H3 T118ph), exists on centromeres and chromosome arms during mitosis. Here, we show that H3 T118ph localizes to centrosomes in humans, flies, and worms during all stages of mitosis. H3 abundance at the centrosome increased upon proteasome inhibition, suggesting that excess free histone H3 localizes to centrosomes for degradation during mitosis. In agreement, we find ubiquitinated H3 specifically during mitosis and within purified centrosomes. These results suggest that targeting of histone H3 to the centrosome for proteasome-mediated degradation is a novel pathway for controlling histone supply, specifically during mitosis.